Stabilization of tie-line power oscillations by robust SMES in interconnected power system with large wind farms - Ngamroo, I.; Cuk Supriyadi, A. N.; Dechanupaprittha, S.; Mitani, Y. (My University, 2009)
This paper proposes a robust controller design of Superconducting Magnetic Energy Storage (SMES) for stabilization of interconnected power systems with wind farms. The inverse additive perturbation is applied to represent system uncertainties such as variation of system parameters, several generating and loading conditions etc. The structure of active and reactive power controllers of SMES is the first-order lead-lag compensator. To tune the controller parameters, the optimization problem is formulated based on the enhancement of additive stability margin. The particle swarm optimization is used to solve for controller parameters. Simulation studies in a six-area interconnected power system with wind farms confirm the robustness of the proposed SMES against various system operating conditions.
Keywords: Inverse additive perturbation; Power system stabilization; Robust control; Superconducting magnetic energy storage; System uncertainties; Wind farms